Natural Product Kuwanon‐L Inhibits HIV‐1 Replication through Multiple Target Binding. (18th January 2017) - Martini, Riccardo; Esposito, Francesca; Corona, Angela; Ferrarese, Roberto; Ceresola, Elisa Rita; Visconti, Laura; Tintori, Cristina; Barbieri, Alessandro; Calcaterra, Andrea; Iovine, Valentina; Canducci, Filippo; Tramontano, Enzo; et al.
Abstract: In recent years many advances have been made in the fight against HIV‐1 infection. However, the lack of a vaccine, together with the increasing resistance to the highly active anti‐retroviral therapy (HAART), make HIV‐1 infection still a serious global emergency. Thus, new compounds with original modes of action are continuously required, and natural products have ever been a very interesting class of pharmacologically active molecules. Some of them have been used since ancient times against viral infections. Here we present a work in which we suggest that kuwanon‐L, a natural product active as an HIV‐1 integrase (IN) inhibitor, might exert its overall antiviral activity through binding to multiple viral targets. Specific enzymatic tests, together with a time‐of‐addition (TOA) experiment, support our hypothesis of binding both to IN and to reverse transcriptase (RT). Overall, this compound can be considered an attractive lead for the development of new classes of antiviral agents able to overcome the problem of resistance, due to its ability to exert its action by binding simultaneously to multiple viral targets. Abstract : Two birds, one stone : We present an unusual time‐of‐addition profile for the natural compound kuwanon‐L (KUW), compatible with the inhibition of two key HIV‐1 enzymes: integrase (IN) and—unexpectedly—reverse transcriptase (RT). Enzymatic assays also showed anti‐RT activity, thus making kuwanon‐L a starting point for a multiple‐target‐binding strategy for potential application against HIV‐1.